Aperture-Fed Quad-Port Dual-Band Dielectric Resonator-MIMO Antenna for Sub-6 GHz 5G and WLAN Application - Trushit Upadhyaya; Ikmo Park; Rajat Pandey; Upesh Patel; Killol Pandya; Arpan Desai; Jayesh Pabari; Gangil Byun; Yogeshwar Kosta (International Journal of Antennas and Propagation)
A four-port dielectric resonator-based connected ground multiple-input multiple-output (MIMO) antenna is designed. The presented antenna was excited through the aperture feeding technique. The dual bands are achieved by optimally feeding the rectangular dielectric resonator through engineered triangular slots. The antenna has operating modes of TE111X and TE111Y at 4.5 GHz and 5 GHz, respectively. It presents a 2 : 1 VSWR bandwidth of 2.64% (4.48 GHz–4.60 GHz) and 1.2% (4.96 GHz–5.04 GHz) in the lower and upper bands, respectively. The edge-to-edge distance between array elements is around 7.5 mm. The single antenna dimension is 30 mm × 30 mm, whereas the four-port antenna dimension is 60 mm × 60 mm. The optimum isolation was achieved by carefully placing the antenna elements on the substrate through multiple iterations. The antenna provides port isolation better than 20 dB at both resonances with full ground profile. The advantage of the antenna is that it provides fair antenna and MIMO parameters without additional isolation techniques. The antenna has efficiency in order of 88.02% and 86.31%. The peak gain is 7.67 dBi and 8.32 dBi at 4.5 GHz and 5 GHz, respectively. The optimum envelope correlation coefficient (ECC) is 0.037, channel capacity coss (CCL) is 0.2 bits/sec/Hz, diversity gain (DG) is 9.99 dB, and total active reflection coefficient (TARC) is −18.87. The antenna elements are orthogonally placed with adequate separation to achieve polarization diversity and spatial diversity. The antenna provides the utilization in Sub-6 GHz 5G and WLAN communication applications.